Early Ipswichian (last interglacial) sea level rise in the channel region: Stone Point Site of Special Scientific Interest, Hampshire, England - Briant, RM; Bates, MR; Boreham, S; Cameron, NG; Coope, GR; Field, MH; M Hatch, M; Holmes, JA; DH Keen, DH; Kilefeather, AA; Penkman, KEH; Simons, RMG; et al. (Elsevier, 2018)
Constraining the speed of sea level rise at the start of an interglacial is important to understanding the size of the ‘window of opportunity’ available for hominin migration. This is particularly important during the last interglacial when there is no evidence for significant hominin occupation anywhere in Britain. There are very few finer grained fossiliferous sequences in the Channel region that can be used to constrain sea level rise and they are preserved only to the north of the Channel, in England. Of these, the sequence at Stone Point SSSI is by far the most complete. Data from this sequence has been previously reported, and discussed at a Quaternary Research Association Field Meeting, where a number of further questions were raised that necessitated further data generation. In this paper, we report new data from this sequence – thin section analysis, isotopic determinations on ostracod shells, new Optical Stimulated Luminescence ages and Amino Acid Recem analyses. These show early sea level rise in this sequence, starting during the pre-temperate vegetation zone IpI, but no early warming. The implications of this almost certainly last interglacial sequence for the human colonisation of Britain and our understanding of the stratigraphic relationship of interglacial estuarine deposits with their related fluvial terrace sequences is explored.